Research Progress on the Mechanism of Baicalein in Scutellaria Baicalensis Against Liver Fibrosis - Wu, Chenyang; Wang, Guotai (Journal of Contemporary Medical Practice, 2025)
Baicalein is a flavonoid extracted from the dried root of Scutellaria baicalensis, family Labiatae, which can inhibit hepatic stellate cell activation, collagen deposition, reduce the release of inflammatory factors, and regulate the cell cycle and apoptosis, thereby controlling the balance between synthesis and catabolism of hepatic extracellular matrix. In this paper, we reviewed the literature on baicalein in the treatment of hepatic fibrosis in recent years and found that baicalein inhibits inflammatory factors such as interleukin and tumor necrosis factor, and regulates the signaling pathways such as transforming growth factor-β, Wnt/β-catenin, nuclear factor-kB, PDGF, MAPK and other related signaling pathways, and then influences the activation of hepatic stellate cells, extracellular matrix deposition, and inhibits the progression of hepatic fibrosis. The aim of this paper is to provide new ideas and a theoretical basis for the treatment of liver fibrosis and the development of new drugs.